PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IIIA SD NEGERI 191 PEKANBARU - Delpika Delpika; Mahmud Alpusari; Zariul Antosa; Elpri Darta Putra (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2019)
This research is based on low science learning achievement of student in class IIIA SD Negeri 191 Pekanbaru with the of students reach KKM is 20.51%. This research is a classroom action research. This research aims to science learning outcomes of students by implementing the cooperative learning model of type Make a Match. There are 39 students in the class, consisting of 21 boys and 18 girls. The instruments of data collection in this study were observation sheets of teacher activities and student activities as well as tests of science learning outcomes. The qualitative analysis showed an improvement of learning process prior to treatment of the first cycle to the second cycle. The result of this research showed an increase in student from the based score with the percentage 20,51%, to 53,85% on the first test and 87,18% on the second test. From the result of this study concluded that cooperative learning model of type make a match can improve the students learning achievement at class IIIA SD Negeri 191 Pekanbaru in the first semester academic years 2018/2019.